Perspective-Taking and Empathic Concern as Mediators for Happiness and Positive Affect in Adolescents With and Without Asperger Syndrome - Rueda-Gallego, Pilar; Fernández-Berrocal, Pablo; Schonert-Reichl, Kimberly (Springer Link, 2014)
The present study explored the mediating role of cognitive and affective components of empathy in the relationship between happiness and positive and negative affect in adolescents with Asperger Syndrome (AS) and their non-AS peers. For that purpose, we measured empathy, subjective happiness, and affect experienced by a group of 42 adolescents with AS compared to 44 of their non-AS peers. Adolescents in both groups were matched on age, sex, and IQ, and were administered a battery of measures assessing their self-reports of empathy, perspective-taking, subjective happiness, and positive and negative affect. Findings revealed that adolescents with AS, in contrast to their peers without AS, reported less subjective happiness, less positive affect, and lower affective balance. No differences were found between the two groups on negative affect. A mediating role of both cognitive and affective components of empathy was found between happiness, positive affect, and affective balance experienced in relation to AS. Theoretical and practical implications of these results are discussed.
Keywords: Asperger, Síndrome de; asperger syndrome; mediators; empathy; affect; happiness